Cadmium, lead and mercury in the blood of workers from recycling sorting facilities in São Paulo, Brazil - Mariana Maleronka Ferron; Rúbia Kuno; Anali Espindola Machado de Campos; Francisco José Viana de Castro; Nelson Gouveia (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
Abstract: Approximately 600,000 people work as recycling material collectors in Brazil and few studies evaluate the health risks involved in this occupation. The objective was to evaluate the blood levels of cadmium (Cd), lead (Pb) and mercury (Hg) among workers from recycling sorting facilities (RSF) in the metropolitan region of São Paulo, Brazil, compare the results with a non-occupationally exposed population, and identify factors associated with higher blood metal levels. Four RSF were selected and 226 collectors were examined for their blood metal levels and associated factors. The mean concentration of Cd (arithmetic mean - AM: 0.47µgL-1; geometric mean - GM: 0.34µgL-1) was almost four times higher than those found in a reference study. The generalized linear model (GLM) indicated that the "RSF where the collectors work", "work in another occupation", and "smoking" were statistically significant predictors of blood Cd levels. The Pb mean concentration (AM: 39.13µgL-1; GM: 34.11µgL-1) was also higher than the observed in the reference study (about 1.4 times) and its associated factors in the GLM were "the RSF where the collectors work", "sex", "smoking", "age" and "meat consumption". The Hg mean concentration (AM: 1.46µgL-1; GM: 0.94µgL-1) was not significantly higher than the reference population and its associated factors were "previous work in other RSF", "fish consumption" and "years of work in the current RSF". This study indicates that recycling material collectors have higher blood Cd and Pb levels compared to the general population.